Perancangan Intranet Untuk Pembelajaran Di Universitas Sahid Surakarta Menggunakan Open Source Software ( Studi Kasus: File Server Universitas Sahid Surakarta) - Putra, Muhammad Arya Priasatama; Susilo, Dahlan; Handoko, Agus Purwo (JURNAL GAUNG INFORMATIKA, 2011)
Intranet is a network of workstations with a local scale without connected to the Internet, while the samba is a set of applications that communicate with Server Massage Block protocol (SMB). SMB is the data communication protocol that provides file and printer sharing and other tasks associated with network. Thesis contains intranetnetwork design for learning at Sahid University in Surakarta, using open source software This research is limited only to the side of applying the samba server in the server for sharing files in order to optimize the learning system on the USS. In this samba server user can have a folder on the samba server. Each user also can log on to domain through the computer any windows that are important in a network. Theprocess of authentication and authorization provided by the samba server as a domain controller in that domain.   This research uses experimental methods in which the writer tries to design a network built on the intranet for learning where teachers could USS distribute materials, substances or value assignment to the students without having to directly face to face. To download a user can enter the application programs run on windows or go into explore menu typing in the address samba server address and the destination for uploading user can use Total Commander application. Sharing a folder so can be done on the Linux operating system and Windows so the two operating systems can communicate with each other to enhance our learning in the USS.